Lean leadership Creating a culture for continuous improvement - Ingelström, Anna; Jivenberg, Björn Steinwall (My University, 2018)
Continuous improvement has been one of the staples of successful industry for years but the research behind what factors separate a successful continuous improvement from a not successful had not been well defined. Both Lean leadership and the factors surrounding it had been defined but only partially explored and the connection between them has seldom been researched. As such, the aim of the thesis was to investigate the separate effect Lean leadership and contextual factors have on a continuous improvement culture and the impact contextual factors have on Lean leadership. The study was conducted by forming an analysis model based on literature which was divided into two sub-models: Enablers and Lean leadership. A case study was performed gathering data from a case company using triangulation in the form of a document study, participant observation and semi-structured interviews. The data formed a write-up of the case which was then compared to the best practices defined in the analysis model in order to gauge the effects. The study resulted in an analysis of what effect the fulfillment level of enablers and Lean leadership have on continuous improvement as well as what effect enablers have on Lean leadership. The conclusions of the analysis for enablers were that unfulfilled enablers negatively impact a continuous improvement culture and that management commitment dominates the negative effect if not fulfilled. For Lean leadership it was found that the individual choices of a Lean leader are important and can have an impact on the continuous improvement culture of those below the leader in the hierarchy. Also, unfulfilled enablers has a direct and adverse effect on a Lean leader’s ability to foster a continuous improvement culture. The study further contributed to theory by an exact description of the effect of these unfulfilled enablers at the case company as well as providing a generalized model for analyzing a continuous improvement culture.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics